Editorial Perspective: Why is there such a mismatch between traditional heritability estimates and molecular genetic findings for behavioural traits?. (1st August 2014) - Thapar, Anita; Harold, Gordon
<x xml:space="preserve">Abstract</x> The puzzle of the disparity between molecular‐ and traditional behaviour genetic study findings has prompted widespread discussion. Fundamental questions have been raised across the whole field of complex genetic traits as well as for behavioural traits. We consider explanations for recent findings and discuss what they mean for the field of developmental psychopathology.